Problems of Complete Systematic Land Registration (PTSL) In The Process of Land Registration In Indonesia - Riza Nurhaidy Rahman (Dinasti Research, 2024)
The legalization of assets with various program names such as PTSL is a continuation of past land administration activities, not too different from village land registration per village in 1961, PRONA, ILAP, and LMPDP. That is, PTSL is a current policy that continues past policies on the translation of Article 19 of the UUPA regarding the state's obligation to register all land in Indonesia. The difference is the packaging and packaging as well as the period or the perpetrator of the policy. We call all these programs as part of land titling, or land administration (legalization/land certification), in order to organize the land administration system. The basic argument is still the same, when the state succeeds in organizing its land administration system, then the data collection is more complete, can minimize, conflict, and give a sense of security to landowners, as well as make it easier for other policy makers. That the ratio-logic implementation of the PTSL program is as a translation of Article 19 of the Basic Agrarian Law on the state's obligation to register all land in Indonesia as well as build new land plot data and at the same time maintain the quality of existing land plot data so that all land plots are registered complete and accurate which provides guarantees of certainty and legal protection of land rights and the guarantee of the location and boundaries of land fields so that it is expected to create a climate of Good investment in Indonesia in accordance with the nawasita of President Joko Widodo. The problem of the implementation of PTSL in Indonesia is the existence of synchronization of regulations between Government Regulation Number 24 of 1997 concerning Land Registration Articles 17, 18 and 19 with the Regulation of the Minister of Agrarian Affairs and Spatial Planning of the Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration of Article 4 paragraph (2) and the PTSL program ignores the tenurial rights of indigenous people, the legal implications of PTSL on customary people's tenure rights in Indonesia is that if the lands of indigenous people are included in the PTSL program, then the customary rights inherent in the community will be destroyed and changed to individual rights only. Article 22 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 6 of 2018 concerning Complete Systematic Land Registration also provides easy requirements for applying for land plot certification so that it is prone to land disputes and conflicts.